Trust, Literasi Media, Kepribadian Hexaco dan Husnudzon Terhadap Kecenderungan Menggunakan Media Sosial - Mardhiah, Desri Rodhiatun; Lutfi, Ikhwan (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2019)
This study was conducted to determine the significance of the influence of trust information, media literacy, HEXACO personality and Husnudzon towards the tendency of using social media for seeking information at student college. The subject of this research was 280 students taken by probability sampling technique, namely cluster sampling. CFA (Confirmatory Factor Analysis) was used to test the validity of measuring instruments and logistic regression analysis is used to test the research hypothesis. The results showed that there was a significant joint effect of trust, media literacy, HEXACO's personality and Husnudzon towards the tendency of using social media for seeking information. Hypothesis test results show that six variables namely trust, structure of media literacy knowledge, personal media literacy locus, extraversion personality type, Husnudzon towards God, and Husnudzon towards others have a significant influence on the tendency of using social media for seeking information. Meanwhile, media literacy competencies, personality types; honesty-humility, emotionality, agreeableness, conscientiousness, and openness to experience do not have a significant influence on the tendency of using social media for seeking information. The results also show the proportion of variance from the tendency of using social media for seeking information explained by all independent variables is 18.0% while the remaining 82.0% is influenced by other variables outside of this study.